"No Longer Interested in Convincing You of My Humanity": Undocuqueer Countervisualities Reclaim the Right to Exist. Issue 4 (1st October 2020) - Cabas-Mijares, Ayleen; Grant, Rachel
Abstract : By examining the images that Undocuqueer activists circulate in online spaces, this study explores how activists rely on visual expression to reveal and reframe the complex forces that shape Undocuqueer life in the United States. Undocuqueer visual communications expose (1) the in-betweenness that defines the Undocuqueer experience, (2) the expanding transnational intersectional coalitions at the foundation of the movement, and (3) a reconceptualization of Undocuqueer worth that is independent from the economic contributions of the community. These countervisualities reclaim what Mirzoeff called the community's right to look and demonstrate alternative forms of self and community that could be more conducive to social transformation and justice .